Pelatihan Pengukuran Kandungan Gizi, Kecukupan Gizi, Nilai Indeks Dan Beban Glikemik Pangan Makanan Populer Malang Raya - Nurul Hakimah; Theresia Puspita; Sutomo Rum Teguh K (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
The number of people with diabetes mellitus (DM) in Indonesia is increasing every year. The proportion in Indoensia is 6,9%, and the precvalence in Malang is 2,3%. Malang as the second largest city in East Java Provice, has geographical conditions, cool weather, and has its own charm. Many popular foods in the Malang Raya area are also traditional Indonesians foods that are rich in taste and color, favored by the community, both as residents and tourits, including : Fried Rice, Grilled Fish, Fried Tofu, Steamed Vegetables, Ice Cream, and Es Teler. This traditional food, which is popular in Malang, has never been measured for its nutrional content, and adequacy, as well as the size of the glycemic index, and glycemic load. The information is needed on the nutritional content, nutritional adequacy, glycemic index, and glycemic load of popular foods to measure the appropriate portion size, as the main health parameters related to DM. The form of community service is given to nutrition alumni of the health polytechnic through training activities related to measurement of nutritional content, glycemic index, and glycemic load of popular foods in Malang Raya, so that later they can assits government efforts in labeling and giving great suggestions for serving, as a form of dissemination, and understanding of foods that meet nutritional content, as well as the value of the glycemic index, and glycemic load are needed in controlling the glycemic response to prevent, and delay the development of complications of DM in the community. The training was carried out in four sessions with the target of nutrition alumni who met the age criteria under 30 years old, had never worked, to increase their knowledge, skills, and confidence in providing KIE to food producing communities. The results of the training showed a significant increase in the knowledge, and skills of nutrition alumni in each session, and gave them better motivation, and self confidens. The next activity is to train them in providing counseling to popular food producers.